Wind tides and surface friction coefficient in semi-enclosed shallow lagoons. (31st August 2021) - Paugam, Caroline; Sous, Damien; Rey, Vincent; Meulé, Samuel; Faure, Vincent; Boutron, Olivier; Luna-Laurent, Emilie; Migne, Emmanuelle
Abstract: The present paper is specifically focused on enclosed or semi-enclosed basins where the wind is the dominant driver of water surface tilting, leading to the so-called wind tide contributing to water levels rise. Wind-induced free surface tilting is studied using the 1-D steady form of the depth-averaged shallow water (Saint-Venant) momentum equation which reflects the depth-averaged local balance between surface slope and wind stress. Two contrasted field sites, the Berre and Vaccarès lagoons, have been monitored providing water level data along a reference axis. This study highlighted the occurrence of wind tides at the two field sites. The bimodal wind exposure ensured the robustness of the observations, with non-linear but symmetric behaviors patterns observed in winds from opposite directions. It is observed that the higher the wind speed, the steeper the slope of the free surface in accordance with the well known basic trend. In addition, a significant effect of depth is observed, with greater surface tilting in the shallower lagoon. The data analysis confirmed the robustness of such a simple approach in the present context. Using the additional assumption of constant, i.e. wind-independent, drag coefficients ( C D ) allowed a good match with the observations for moderate wind speeds for both sites. However, the depth effect required the C D to be increased in the shallower basin. Classical empirical wind-dependent C D parameterizations provide better wind-tide predictions than the constant- C D approach in very strong wind conditions but totally failed in predicting surface tilting in the shallower site, suggesting that physical parameters other than wind speed should be taken into account for the C D parameterization in very shallow lagoons. Highlights: A comparative experimental study of wind-tides in two coastal shallow lagoons. Wind effects are well predicted using 1-D steady depth-averaged momentum balance theoretical estimation. Constant surface drag coefficients show a better performance than wind-dependent formulations. Depth-effect affects surface processes, affecting the drag and the wind-tide amplitude.